(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2019)
Digitalization is the core driving force of the fourth industrial revolution. This new era will result in paradigm shift in production and in marketing of products and services. The smarter production can make value creation easier with reducing the cost of manufacturing and with producing better quality. It will enable a more customized even personalized production. The digitalization driven paradigm shift will make it possible to personalize also the marketing tools, like pricing, distribution, communication, customer management, and customer experience, which embraces all interaction between the seller and the customers. The aim of this conceptual study is to discuss the definition and role of customer experience (CX) in the today’s digital world and draw the attention to this issue in the Central and Easter-European countries where CX theory and practice seems to be lagging behind the Western countries. To exploit the new possibilities of customer experience companies must understand how the customer decision journey has changed and they have to map and explore those new touchpoints, which determine customers’ purchasing decisions. The issue of the new methods of customer experience brings up also new ethical questions, like the contradiction between the data need of personalization about customers, and the need to prevent their privacy against intruding. This “catch 22” will also be discussed in the study. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.